KARAKTERISTIK FISIK DAN SENSORI VIRGIN COCONUT OIL DENGAN PENAMBAHAN FILTRAT JAHE - Sipahelut, Sophia G; Rejeki, Sri (Jurnal Sains dan Teknologi Pangan, 2021)
ABSTRACT The purpose of this study was to determine the concentration of ginger addition that can produce VCO with high yield, refractive index, and specific gravity that met quality standards and was preferred by consumers. The research design used a completely randomized design with treatments J1 (10% ginger), J2 (20% ginger), and J3 (30% ginger). Data analysis used the One-Way Analysis of Variance (ANOVA) method using SPSS software version 17. The significant results were then followed by Duncan's Multiple Range Test (DMRT) at a significance level of 0.05. The results show that the most preferred treatment was J1 with average hedonic scores of color, aroma, taste, texture reached 4.85 (very like), 4.45 (like), 4.25 (like), and 4.35 (like), respectively. Meanwhile, the descriptive scores of color, aroma, taste, and texture reached 2.25 (a little yellowish), 3.60 (had ginger aroma), 3.30 (slightly spicy), and 2.45 (slightly thick). The selected product had a 22% yield, 0.953 specific gravity, and 1.446 refractive indexes. Yield and specific gravity results met the Asian and Pacific Coconut Community (APCC) standard but the refractive index did not. Keywords: ginger, physical characteristic, sensory characteristic, virgin coconut oil ABSTRAK Tujuan penelitian ini adalah menentukan konsentrasi penambahan jahe yang dapat menghasilkan VCO dengan rendemen tinggi, indeks bias dan bobos jenis sesuai standar mutu serta disukai konsumen. Rancangan penelitian menggunakan Rancangan Acak Lengkap dengan perlakuan J1(10% jahe), 2(20% jahe) dan J3(30% jahe). Analisis data menggunakan analisis dengan metode One Way Analysis of Variance (ANOVA) menggunakan software SPSS versi 17. Hasil analisis terdapat pengaruh oleh perlakuan, dilanjutkan dengan Duncans Multiple RangeTes t(DMRT) pada taraf signifikansi α=0.05. Hasil penelitian menunjukkan perlakuan terpilih pada J1 dengan rerata hedonik warna 4,85 (sangat suka), aroma 4,45 (suka), rasa 4,25 (suka), tekstur 4,35 (suka), deskriptif warna 2,25 (agak kekuningan), aroma 3,60(beraroma jahe), rasa 3,30 (agak pedas jahe), tekstur 2,45 (agak kental), rendemen 22%, bobot jenis 0,953 dan indeks bias 1,446. Uji rendemen dan bobot jenis telah memenuhi Asian and Pacific Coconut Community (APCC) namun indeks bias belum memenuhi standar APCC. Kata Kunci: jahe, sifat fisik, sifat sensoris,virgin coconut oi